The Role of Organizational Culture in Improving the Performance of Company Marketing Strategy - A Nazalia Ramadhani We Tenripada; Enang Suherman; Arfandi Arfandi; Annisa Almagfira; Nurul Sriwindayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study aims to analyze the role of organizational culture in improving the performance of corporate marketing strategies. In an increasingly competitive business environment, companies are required to implement effective and innovative marketing strategies supported by a strong organizational culture. Organizational culture plays a crucial role in shaping values, norms, and work behaviors that enhance marketing performance. This research employs a qualitative approach using a literature review method. Data were collected from secondary sources such as academic journals, books, and other relevant publications. The analysis was conducted using descriptive and comparative techniques to examine the relationships between organizational culture, innovation, and marketing strategy performance. The findings indicate that organizational culture plays a significant role in improving marketing strategy performance, both directly and indirectly through innovation as a mediating variable. A culture that supports creativity, collaboration, and market orientation encourages sustainable innovation. The study concludes that a strong and adaptive organizational culture can enhance marketing effectiveness and improve a company’s competitive advantage